Perancangan dan Pengujian Prototipe Alat Desalinasi Air Laut Berbasis Energi Surya untuk Produksi Air Tawar: (Studi Kasus Wilayah Pesisir Desa Karampuang, Kecamatan Mamuju) - Syaiful, Syaiful; H, Idham (Universitas Muhammadiyah Kendari, 2026)
The developed desalination device prototype has the potential to serve as appropriate technology for clean water supply in coastal areas. However, further development is needed to improve the device’s efficiency and performance stability under various environmental conditions. This study aims to design and test the performance of a solar-powered seawater desalination prototype as a solution for clean water supply in coastal areas. The method used is an experimental approach through the stages of design, fabrication, and testing of the device under real-world environmental conditions. The desalination process is carried out through evaporation and condensation mechanisms using a solar still system. The results of the study indicate that the device is capable of producing freshwater with an efficiency influenced by the input water volume, temperature, and solar radiation intensity. The highest efficiency of 90% was achieved with an input volume of 4 liters under sunny weather conditions. The use of an aluminum reflector was proven to increase the system temperature to 84°C, thereby accelerating the evaporation process. Overall, the developed desalination device has the potential to serve as an appropriate technology in coastal areas.